Cognitive Linguistics: Ideology and Critical Discourse Analysis - elmellakh, mhammed (El Omda in Linguistics and Discourse Analysis, 2019)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:32c27e8d-0406-4310-8c57-7cfb6e3aa634-62" data-testid="conversation-turn-126" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="6c84d9bf-af50-499a-bb9b-07a66a2d3325" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> Interest in ideology and discourse has grown among scholars working within the framework of cognitive linguistics. This study aims to provide an overview of the key contributions and perspectives that the theoretical approach of cognitive linguistics can offer, regardless of the analytical methods employed by critical discourse analysts. It seeks to examine more deeply the integrative relationship between cognitive linguistics and critical discourse analysis. Given the alignment of cognitive linguistics with critical discourse analysis, this overview of research on the linguistics of ideology intends to explicitly and implicitly reinforce the shared concerns between these two research frameworks.